Translation Techniques Applied for Cultural Terms in Harry the Order of the Phoenix Written by J.K. Rowling - Hasibuan, Zainuddin (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2025)
ABSTRACT This research analyzes the translation techniques applied to 10 selected cultural terms from Harry Potter and the Order of the Phoenix by J.K. Rowling, translated into Indonesian. The research employs a descriptive qualitative method, utilizing Molina and Albir’s (2002) framework to identify translation techniques. The analysis focuses on how these techniques preserve the meaning and contextual relevance of cultural concepts for readers. Research results indicate that there are ten data which has been analysed in this research which consists of ten translation techniques. They are literal, calque, transposition, modulation, amplification, borrowing, description, reduction, adaptation, and additions. The data indicate that 40% of the terms were translated using couplet techniques which consists of 4 data, 40% with triplet techniques which also consists of 4 data, and 10% with single techniques which consists of 2 data. The study highlights the contribution of combining techniques to maintain linguistic and cultural accuracy. It emphasizes the need for translators to consider the socio-cultural and contextual implications of the terms to enhance comprehension and readability for Indonesian audiences. The research offers practical recommendations for translators working on literary texts, bridging linguistic and cultural gaps, and advancing cross-cultural understanding in the field of cultural studies.